PANCASILA, KEARIFAN LOKAL DAN PENGEMBANGAN DAERAH - Asrom, Hafidh (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2007)
In this paper, Pancasila, local wisdom and regional development are critically analyzed from the perspective of regional representative board. It was a real situation that the emergence of central-regional dichotomies in the terminology of â€œcapitalistic developmentâ€ was continuously designed by the new order regime. As its result, the dichotomy emerged unproductive impacts for Indonesian community in the region. The regional developmentâ€™s mission should be understood as an effort of regional autonomy stabilization, primarily in the implementation of development and government tasks, acceleration of regional development by strengthening and raising â€œcapacity for competenceâ€ as a foundation of regional growth. Therefore, the regional development is proposed to develop and strengthen the government in accordance with the regional autonomy implementation such as realistic, dynamic, harmonious, and responsible governance.